Epidemiological investigation of COVID-19 transmission at takziah cluster: The case from Gunungkidul Yogyakarta - Adiratna, Widia (BKM Public Health and Community Medicine, 2021)
Objective: Up to 1.5 years of the pandemic, Gunungkidul Regency reported approximately 12 types of clusters, one of which was the Takziah Cluster in Dusun Panggang I, Giriharjo, Panggang. On March 27, 2021, the Gunungkidul Regency Health Office received a report of 6 people from a family who were symptomatic with positive RT-PCR results. It is known that the family head of the family died with probable status. Epidemiological investigations are carried out to determine the magnitude of the problem, contact history with the suspect, and prevent the spread of the case. Method: This research uses a descriptive approach. Cases are people in Dusun Panggang I who have an epidemiological relationship with people who take part in takziah activities with positive RT-PCR results. Data were collected by interview and secondary data obtained from the Puskesmas and the Health Office. Results: Cases started from probable who were buried without a health protocol. A total of 40 confirmed cases were found through mass screening of 630 residents on March 27- April 26, 2021 (Attack Rate=6.50%) with 2 deaths (Case Fatality Rate=4.88%). The majority of cases were women (73.17%) and aged >60 years (41.46%). The most common symptoms experienced were fever (43.34%), cough (34.15%), and fatigue (29.3%). From the interviews, family and neighbors gather to cook and mourn without maintaining distance, and wearing masks are not correct. Conclusions: There has been a transmission of COVID-19 in Dusun Panggang I caused by a takziah event. The lack of proper use of masks and crowding without keeping a distance is one of the risk factors for transmission during takziah. Takziah by following health protocols is mandatory during the COVID-19 pandemic. Education and clear enforcement of regulations from local governments are very much needed.